(untitled) (American Journal of Islam and Society, 2014)
This monograph challenges the notion that Islam is, at its core, an intolerant religion. Through a careful reading of the Qur’an, the Hadith literature, and extra-canonical texts, as well as examples from history, Reza Shah-Kazemi argues that Islam is rooted in an inclusivist ethic that permeates the founda- tions of Islamic belief and practice. He provides numerous examples of how Muslims have behaved in accordance with the Islamic values of unity (tawḥīd), mercy (raḥmān), and compassion (raḥmah) elucidated in the Qur’an and the Hadith, and illustrated in history from the early Islamic period to recent centuries. This volume provides an academic and sophisticated reading of tolerance in Muslim history that is accessible to the scholar, student, and layperson interested in how Islam deals with religious minorities. The introduction begins with the proposal that Islam is, at its foundation, committed to the principle of religious pluralism. Backed by eminent thinkers, including Wilfred Cantwell Smith (d. 2000) and John Locke (d. 1704), Shah- Kazemi describes this principle in terms of the “inalienable dignity” of all human beings as cited in Q. 30:30 and Q. 17:70: “We have bestowed dignity on the progeny of Adam [and Eve]” (p. 12). Examples of this principle are seen in the behavior of the Prophet as well as in that of his cousin and son-in-law Ali ibn Abi Talib, individuals who, in the author’s perspective, communicated the rule of compassion (raḥmah) throughout their lives. At the conclusion of this chapter, the author suggests that this practice be revived, for it accords with western secular principles that are not “an expression of its own specifically religious traditions,” but rather a result of the intra-religious wars that accompanied the Reformation. Shah-Kazemi uses the rest of this volume to elucidate this spirit, which is best expressed in Q. 49:13: “O humanity, We have created you male and female, and We have made you into tribes and nations in order that you might come to know one another” (p. 19) ...